The effects of ibuprofen on muscle hypertrophy, strength, and soreness during resistance training - Krentz, J. R.; Quest, B.; Farthing, J. P.; Quest, D. W.; Chilibeck, P. D. (Applied Physiology, Nutrition, and Metabolism, 2008)
High doses of ibuprofen have been shown to inhibit muscle protein synthesis after a bout of resistance exercise. We determined the effect of a moderate dose of ibuprofen (400 mg/d) consumed on a daily basis after resistance training on muscle hypertrophy and strength. Twelve males and 6 females (~24 years of age) trained their right and left biceps on alternate days (6 sets of 4-10 repetitions), 5 d/week, for 6 weeks. In a counter-balanced, double-blind design, they were randomized to receive 400 mg/d ibuprofen immediately after training their left or right arm, and a placebo after training the opposite arm the following day. Before- and after-training muscle thickness of both biceps was measured using ultrasound and 1 repetition maximum (1 RM) arm curl strength was determined on both arms. Subjects rated their muscle soreness daily. There were time main effects for muscle thickness and strength (p < 0.01). Ibuprofen consumption had no effect on muscle hypertrophy (muscle thickness of biceps for arm receiving ibuprofen: pre 3.63 ± 0.14, post 3.92 ± 0.15 cm; and placebo: pre 3.62 ± 0.15, post 3.90 ± 0.15 cm) and strength (1 RM of arm receiving ibuprofen: pre 18.6 ± 2.8, post 23.4 ± 3.5 kg; and placebo: pre 18.8 ± 2.8, post 22.8 ± 3.4 kg). Muscle soreness was elevated during the first week of training only, but was not different between the ibuprofen and placebo arm. We conclude that a moderate dose of ibuprofen ingested after repeated resistance training sessions does not impair muscle hypertrophy or strength and does not affect ratings of muscle soreness.